Long-term behaviour of ceramic powder containing concrete for pavement blocks. Issue 14 (6th December 2021) - Reiterman, Pavel; Holčapek, Ondřej; Jaskulski, Roman; Kubissa, Wojciech
ABSTRACT: The present paper deals with the long-term experimental study focusing on the properties of concrete mixtures with the addition of ceramic powder, which originate during the hollow brick production. The used ceramic powder was applied as Portland cement replacement up to 30 wt.%. The properties of concrete were evaluated in terms of fresh mixture parameters, mechanical, permeability and durability properties based on the accelerated testing. The progress of the pozzolanic reaction was monitored using thermal analysis. Higher dosage of ceramic powder caused a significant loss of workability and an increase of permeability, which were declared on the results of carbonation test and freeze–thaw cycling. However, a mixture with 25 wt.% replacement exhibited values similar to the control mixture after 3 years. The production of vibro-pressed concrete pavement element was selected for industrial testing due to the reduced workability. However, only 15 wt.% replacement was applied for the operational tests, which were evaluated in terms of split strength after 5 days and freeze–thaw cycling after 28 days. Industrially produced specimens exhibited similar or higher values of studied parameters in comparison to the control mixture. Long-term mechanical tests and freeze–thaw cycling confirmed great practical potential of ceramic powder for these type of elements.